Has feminism changed science? - Schiebinger, Londa (Signs, 2000)
Discusses whether the presence of feminism in science has changed science, discounting the idea that simply encouraging more women to enter science will necessarily produce change and stressing the need for governmental funding and initiatives on women and gender in science. Argues for multiple arenas for change (research priorities, domestic relations, university structures, classroom practices, and home-work relationships.)
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; histoire et politique; projet charge mentale; pédagogie; périodes historiques; recherches féministes; régions géographiques; thématiques; travail; états-unis